Comparison of the Efficacy of Digital Caliper and a Newly Designed Digital Bone Gauge for Measurement of Edentulous Alveolar Ridge Width - Amid, Reza; Rahimipour, Kasra; Namdari, Mahshid; Kadkhodazadeh, Mahdi (Journal of Dental School, 2019)
Objectives: An efficient, safe, affordable and easily accessible measuring instrument for quantitative assessment of bone prior to dental implant placement enables more accurate treatment planning. Costly imaging modalities are neither widely available, nor affordable for some patients. This study sought to assess the efficacy of a newly designed digital bone gauge for measurement of bone width with 0.1 mm accuracy in comparison with a digital caliper. Methods: Using CATIA software, three-dimensional (3D) model of the instrument was designed and its experimental version was fabricated in two models and tested on an edentulous alveolar ridge model. The efficacy of the instrument was assessed by comparing the values obtained by the designed bone gauge with direct measurements made by a digital caliper. The buccolingual width of the edentulous ridge was measured at the crestal level and at 1, 2, 3 and 4 mm apical to the bone crest by the designed bone gauge and digital caliper. The intraclass correlation coefficient (ICC) of the values was calculated. Results: Virtual and experimental models of the instrument were designed and patented. The designed instrument was successfully capable of measuring bone width with 0.1 mm accuracy. The ICC values at 1, 2, 3 and 4 mm apical to the bone crest and at all levels were calculated to be 0.973, 0.994, 0.997, 0.998 and 0.998, respectively. Conclusion: The designed digital bone gauge can efficiently measure bone width at different levels with high accuracy. It can provide valuable and reliable information about bone width at initial clinical examination.